On applications of Andrica-Badea and Nagy inequalities in spectral graph theory - MILOVANOVIĆ, Igor; MILOVANOVIĆ, Emina; GLOGIĆ, Edin (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
Applications of Andrica-Badea and Nagy inequalities for determining bounds of graph invariants of undirected, connected graphs are investigated. We consider bounds of the following invariants: the first Zagreb index, general Randic index, Laplacian linear spread and normalized Laplacian spread of graphs. Mathematics Subject Classification (2010): 60E15, 05C50.